Geospatial Assessment of Coseismic Landslides in Baturagung Area - Saputra, Aditya; Sartohadi, Junun; Hadmoko, Danang Sri; Gomez, Christopher (Universitas Muhammadiyah Surakarta, 2015)
Java, the most densely populated island in Indonesia, is located on top of the most seismically active areas in Southeast Asia: the Sunda Megathrust. This area is frequently hit by strong earthquake. More than 3,300 M>5earthquakesoccurred between 1973-2014. The wide range of mountainous areas and high intensity of rainfall, make several part of the island one of the most exposed regions for coseismic landslides such as Baturagung area, the Southeast mountainous area of Yogyakarta Province. An integrated method between RS and GIS was used to conduct the vulnerability assessment due to the lack of the site specific slope instability analysis and coseismic landslides data. The seismic zonation of Baturagung area was obtained based on the analysis of Kanai attenuation. The geologic information was extracted using remote sensing interpretation based on the 1:100,000 geologic map of Yogyakarta and geomorphologic map of Baturagung area as well. The coseismic landslide hazard assessment has been estimated using scoring analysis in the GIS platform proposed by Mora and Vahrson (1993) with several modification. The accomplished coseismic landslide hazard map shows medium hazard coverage in the eastern areas, in the upper slope of Baturagung area, which consists of Semilir Formation. The result provides a distinct description of coseismic landslides hazard distribution in Batuaragung area. However, it should only be the preliminary assessment of the site specific investigation especially on valuable area or asset.Â